(untitled) (Journal of Libya for geographical studies, 2025)
This paper discussed the analysis of the hydrological variables of Wadi Al-Qud Basin and their impact on Al-Marj Plain. It aimed to identify the geomorphology of Wadi Al-Qud Basin, estimate its surface runoff, hydrological coefficients, and analyze the changes that occurred in the area and volume of water in Umm Al-Makhali Pond in Al-Marj Plain. The study relied on several approaches, including the analytical approach using geographic information systems software, applying statistical analysis methods to extract results related to the topographic areas and the drainage network. Among the most important results reached by this study is that the discharge rate in Wadi Al-Qud Basin is 50.3 m³/second, while the discharge volume reached 7938.5 m³/second, and the total volume of surface runoff in the entire Wadi Al-Qud Basin reached 30.42 km³/year. The highest precipitation was in 1975 (530.9 mm), and the flooded area was less compared to 2019, which witnessed less precipitation (319.8 mm) but a larger flooded area. The study concluded with a set of recommendations that may contribute to alleviating the severity of the problem